The Role of Vti1a in Biological Functions and Its Possible Role in Nervous System Disorders - Tang, Fajuan; Fan, Jiali; Zhang, Xiaoyan; Zou, Zhuan; Xiao, Dongqiong; Li, Xihong (Frontiers in Molecular Neuroscience, 2022)
Vesicle transport through interaction with t-SNAREs 1A (Vti1a), a member of the N-ethylmaleimide-sensitive factor attachment protein receptor protein family, is involved in cell signaling as a vesicular protein and mediates vesicle trafficking. Vti1a appears to have specific roles in neural system, primarily by regulating upstream neurosecretory events that mediate exocytotic proteins and the availability of secretory organelles, as well as regulating spontaneous synaptic transmission and postsynaptic efficacy to control neurosecretion. Vti1a also has essential roles in neural development, autophagy, and unconventional extracellular transport of neurons. Studies have shown that Vti1a dysfunction plays critical roles in pathological mechanisms or treating of Depression, Parkinson's disease, and Hepatic encephalopathy by influencing spontaneous neurotransmission. It also may have an unknown role in amyotrophic lateral sclerosis. A VTI1A variant is associated with the risk of glioma, and the fusion product of the VTI1A gene and the adjacent TCF7L2 gene is involved in glioma development. This review summarizes Vti1a functions in the nervous system and highlights the role of Vti1a in the several nervous system disorders.